Effect of aerobic exercise on physical performance in patients with Alzheimer's disease. Issue 12 (23rd June 2016) - Sobol, Nanna Aue; Hoffmann, Kristine; Frederiksen, Kristian Steen; Vogel, Asmus; Vestergaard, Karsten; Brændgaard, Hans; Gottrup, Hanne; Lolk, Annette; Wermuth, Lene; Jakobsen, Søren; Laugesen, Lars; Gergelyffy, Robert; et al.
Abstract: Introduction: Knowledge about the feasibility and effects of exercise programs to persons with Alzheimer's disease is lacking. This study investigated the effect of aerobic exercise on physical performance in community‐dwelling persons with mild Alzheimer's disease. Methods: The single blinded multi‐center RCT (ADEX) included 200 patients, median age 71 yrs (50‐89). The intervention group received supervised moderate‐to‐high intensity aerobic exercise 1 hour × 3/week for 16 weeks. Assessments included cardiorespiratory fitness, single‐task physical performance, dual‐task performance and exercise self‐efficacy. Results: Significant between‐group differences in change from baseline (mean [95%CI]) favored the intervention group for cardiorespiratory fitness (4.0 [2.3‐5.8] ml/kg/min, P <0.0001) and exercise self‐efficacy (1.7 [0.5‐2.8] points, P =0.004). Furthermore, an exercise attendance of ≥66.6% resulted in significant positive effects on single‐task physical performance and dual‐task performance. Discussion: Aerobic exercise has the potential to improve cardiorespiratory fitness, single‐task physical performance, dual‐task performance and exercise self‐efficacy in community‐dwelling patients with mild Alzheimer's disease. Highlights: Aerobic exercise is feasible in home‐dwelling patients with Alzheimer's disease (AD) Aerobic exercise improves cardiorespiratory fitness in patients with AD Exercise improves single‐task physical performance and dual‐task performance in patients with AD Exercise contributes to higher levels of exercise self‐efficacy in patients with AD Exercise may postpone the loss of physical independence in patients with AD